PENERAPAN MANAJEMEN KURIKULUM PADA SEKOLAH FULL DAY DI SDIT CAHAYA HATI KOTA BUKITTINGGI - Dalvi Dalvi (IAIN Batusangkar, 2016)
Application Management Curriculum In School Full Day In SDIT Cahaya Hati Kota Bukittinggi. Outonomy of education is giving an authority to developing our school throuhg some rules which is supporting student quality in learning proces. The final result from this education is to produce the students who was competency based on the expectation from the stakeholder as a user of graduates and also for goverment it self to realize this, one of the most important component is a curriculum. To produce the good curriculum it is also needed a good management. Curriculum management can be different between one institiation and the others education instituation, as aplied in full day school.Kata Kunci: penerapan, managemen kurikulum, sekolah full day